The Multinational Corporation and Industrial Relations : The American Approach - Heise, Paul (Relations industrielles / Industrial Relations, 1973)
The special problems that the MNC presents in the context of the American industrial relations system has led the U.S. unions, to respond with a call for controls on trade. Europeans, in a different context, are responding to the integration of Europe and the imposition of some aspects of the U.S. system by U.S. corporations in Europe. The problems of understanding each other's goals will be difficult, but controls on the MNCs could serve both.